Muscle Synergy Alteration of Human During Walking With Lower Limb Exoskeleton - Li, Zhan; Liu, Huxian; Yin, Ziguang; Chen, Kejia (Frontiers in Neuroscience, 2019)
Muscle synergy reflects inherent coordination patterns of muscle groups as the human body finishes required movement. It may be still unknown whether the original muscle synergy of people may alter or not when exoskeletons are put on for subjects during their normal walking activities. This paper reports the experimental results and presents analysis of muscle synergy on 17 able-bodied subjects with and without wearing lower-limb exoskeletons when they perform normal walking tasks. The electromyography (EMG) signals of tibialis anterior (TA), soleus (SOL), lateral gastrocnemius (GAS), vastus medialis oblique (VMO), vastus lateralis oblique (VLO), biceps femoris (BICE), semitendinosus (SEMI), and rectus femoris (RECT) muscles are extracted to obtain the muscle synergy. The quantitative results show that, when the subjects wear exoskeletons to walk normally, their mean muscle synergy is evidently changed from the one as they walk without exoskeletons. When the subjects walk with and without exoskeletons, statistical significance differences on sub-patterns of muscles' synergies in the corresponding two groups can be found.